The Impact of Cross Cultural Language Barriers in Patient Care Delivery - Julawong, Orawan; Kamolsilp, Chantana; Pansri, Supunnika; Eaksamai, Suwaluck (Journal of The Royal Thai Army Nurses, 2019)
Society has seen rapid changes in the last decade. The consequences of these changes have made acclimating to a different culture more complicated for people with diverse values, beliefs, and religious orientations. It is necessary that nursing professionals adjust health care delivery in ways that recognize & accommodate the basic needs of a wide variety of patients. Cultural diversity, especially with cross cultural language, cannot be avoided. Nurses are critical health care team members who would often be the first group who make contact with patients. If these nurses lack the knowledge and skills to communicate with patients with differing cultural orientation & perspectives, the end result may bring harm or life-threatening consequences entrusted to their care. Thus, the nurses must have good cultural competency in order to deliver high quality in all aspects of care.